DIGITAL-BASED LAND SERVICE INNOVATION: ELECTRONIC CERTIFICATE CHECKING AT THE KLATEN DISTRICT LAND OFFICE - Tri Mardiyanti; Kristina Setyowati; Sudarmo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
With the rapid development of science and technology, the government is expected to innovate in providing public services to achieve Good Governance. One example of the application of Good Governance is public services in the land sector managed by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency. As part of this government agency, the Klaten Regency Land Office developed an innovation in online certificate checking services. The purpose of this study was to determine the extent of the implementation of online certificate checking service innovations and what factors influenced it. The method used in this study is a qualitative descriptive method. The data collection method in this study used interviews and document reviews where the informant sources were the community and employees of the Klaten Regency Land Office. Data analysis in this study consisted of three stages: data condensation, data presentation, and drawing conclusions or verification. The results of the study indicate that online certificate checking services can significantly improve the quality of the Klaten Regency Land Office in providing fast, accurate, transparent, and accountable services to applicants or the community. The public has responded positively to the shift towards digital-based land service innovations, particularly in online certificate verification. The research findings provide insights into these service innovations and the factors influencing them. These factors can be categorized as internal factors, such as vision and strategy, human resources, organizational structure, and organizational culture, and external factors, such as technology availability and government policies. Recommendations from this research aim to develop more robust and sustainable programs for public service innovation in the future.